2021
DOI: 10.1177/14644207211020401
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective optimization of process variables in single-point incremental forming using grey relational analysis coupled with entropy weights

Abstract: Incremental sheet forming is a specific group of sheet forming methods that enable the manufacture of complex parts utilizing computer numerical control instead of specialized tools. It is an incredibly adaptable operation that involves minimal usage of sophisticated tools, dies, and forming presses. Besides its main application in the field of rapid prototyping, incremental sheet forming processes can be used for the manufacture of unique parts in small batches. The goal of this study is to broaden the knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Dabwan et al [12]conducted multiobjective optimization in SPIF using GRA coupled with entropy analysis. Ajay et al [13]studies SPIF of titanium alloy sheets.…”
Section: Durante Et Al[6]compared Experimental and Analytical Results...mentioning
confidence: 99%
“…Dabwan et al [12]conducted multiobjective optimization in SPIF using GRA coupled with entropy analysis. Ajay et al [13]studies SPIF of titanium alloy sheets.…”
Section: Durante Et Al[6]compared Experimental and Analytical Results...mentioning
confidence: 99%
“…Grey relational analysis (GRA) with entropy weights can solve multi-response optimization problems involving multiple criteria, and its use in multi-response problems has acquired popularity [25][26][27]. Dabwan et al [28] applied the grey relational method with entropy weights to identify the optimal process parameters for single-point incremental forming products and found that the tool diameter has the greatest effect on the thinning of the single-point incremental forming process. She et al [29] optimized the bending performance of optical fibers by employing grey relational analysis and discovered that the bending loss decreased by an order of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of the forming behaviour under different processes like stretch forming, 16,17 deep drawing 18,19 and incremental sheet metal forming 20,21 is essential as the material undergoes different deformation modes under these processes. Especially, the investigation of the deep drawing behaviour of CP Ti is of much interest for the fabrication of sheet metal components.…”
Section: Introductionmentioning
confidence: 99%